Characteristics of Nitrogen-Fixing Bacteria Isolated from the Rhizosphere at Kaolin Lake, Belitung, Indonesia - Nurhakiki; Rusmana, Iman; Astuti, Rika Indri (Bogor Agricultural University, Indonesia, 2025)
Former kaolin mining has poor physical and chemical properties for plants. The low nutrient content makes difficult for plants to grow. Nitrogen (N2) is an important macronutrient for plants, but it can only be absorbed in the form of ammonium ions (NH4+) or nitrate ions (NO3-). Therefore, it is necessary to transform nitrogen, which is able to change the molecular form so that it can be absorbed by plants. The strategy that can be done is using nitrogen-fixing bacteria. This study aimed to explore and analyze the diversity of nitrogen-fixing bacteria based on 16S rRNA and nifH gene from the rhizosphere of the Kaolin Lake area. The method started with bacterial isolation from rhizosphere soil samples. Selected isolates were tested for ammonium content to determine the ability of isolates to fix nitrogen. In this study, 13 isolates had the ability to fix nitrogen, two of which had a high ammonium concentration, namely RBN 5.6, and RBA 2.3. The highest ammonium concentration was produced by isolate RBN5.6 amounting to 7.55 μg/ml. Based on 16S rRNA gene identification, isolate RBN5.6 was similar to Burkholderia cepacia and isolate RBA2.3 was similar to Bacillus aquimaris. Based on the detection of the nifH gene, isolate RBN5.6 was identified as a protein-encoding dinitrogenase reductase gene group cluster from the Stutzerimonas stutzeri.